2022
DOI: 10.1016/j.jbc.2022.101621
|View full text |Cite
|
Sign up to set email alerts
|

The P300 acetyltransferase inhibitor C646 promotes membrane translocation of insulin receptor protein substrate and interaction with the insulin receptor

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In agreement, when LPS-stimulated acute inflammation mice were preinjected with p300 inhibitors, acetylation of p65 Lys310 and expression of pro-inflammatory factors in peritoneal macrophages were virtually unchanged after BBR treatment. HFD feeding increased p300 protein levels in the liver of mice, while treatment with the p300-specific inhibitor C646 significantly increased insulin sensitivity and glucose tolerance as well as phosphorylation levels of AKT and GSK3 in the liver of HFD-induced obese mice [ 48 , 49 ]. These results indicate that the inhibition of p300 might be a therapeutic mechanism for the association between berberine and obesity in the adipose tissues of obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, when LPS-stimulated acute inflammation mice were preinjected with p300 inhibitors, acetylation of p65 Lys310 and expression of pro-inflammatory factors in peritoneal macrophages were virtually unchanged after BBR treatment. HFD feeding increased p300 protein levels in the liver of mice, while treatment with the p300-specific inhibitor C646 significantly increased insulin sensitivity and glucose tolerance as well as phosphorylation levels of AKT and GSK3 in the liver of HFD-induced obese mice [ 48 , 49 ]. These results indicate that the inhibition of p300 might be a therapeutic mechanism for the association between berberine and obesity in the adipose tissues of obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse primary hepatocytes were cultured in William’s medium E supplemented with ITS (BD Biosciences) and dexamethasone ( 32 ). After 16 h of planting, adenoviral shRNAs were added.…”
Section: Methodsmentioning
confidence: 99%
“…407 C646 is a specific inhibitor of P300 acetyltransferase; it suppresses the acetylation of IRS1/2 and promotes IRS1/2 membrane translocation, resulting in insulin signalling pathway activation. 408 Resveratrol is a natural polyphenolic compound and could be used to treat metabolic diseases by activating SIRT1. Bagul et al 409 indicated that resveratrol alleviates cardiac oxidative stress in diabetes by activating SIRT1, which deacetylates H3 at lysine 9 and NF-κB-p65 at lysine 310.…”
Section: Epigenetic Therapymentioning
confidence: 99%